A Storm on the Horizon? "Twister" and the Implications of the Blockchain and Peer-to-Peer Social Networks for Online Violent Extremism. - Mott, Gareth (Studies in Conflict & Terrorism, 2019)
"Twister," developed by Miguel Freitas, is a social network platform centered around micro-blogging, much like Twitter. However, rather than relying on centralized servers owned and maintained by a single firm, Twister users operate a blockchain combined with distributed hash table (DHT)–like and BitTorrent-like protocols to both make posts and send private messages, and also to receive entries from other users. Twister's raison d'etre is that it offers a social networking platform that cannot be censored and cannot itself censor. The software does not record the Internet Protocol addresses users use to access the service, nor does it notify other users of an account's online/offline status. Growing adoption of blockchain services means that it is possible that the concept of decentralized social networks could become a norm. It is suggested in this article that blockchain-based peer-to-peer social networks present challenges to the current counterextremist practices for content removal and censorship. While there are methods to disrupt usage of blockchain-based peer-to-peer services, these approaches may have the net harm of curtailing bona fide use of legal and novel technologies. Given this opportunity cost, non-transitory online violent extremist content may need to be tolerated.